Ultrasound Detection of Intracranial Hypertension in Brain Injuries - Vitiello, Livio; Salerno, Giulio; De Bernardo, Maddalena; D'Aniello, Olga; Capasso, Luigi; Marotta, Giuseppe; Rosa, Nicola (Frontiers in Medicine, 2022)
In recent years, the measurement of optic nerve sheath diameter with ultrasound to detect the presence of increased intracranial pressure has widely spread. It can be qualitatively and effectively used to identify intracranial hypertension. Intracranial pressure can rise due to acute injury, cerebral bleeding, hydrocephalus, brain tumors and other space-occupying abnormalities, and it is linked to a high death rate. The purpose of this review is to give a general overview of the most relevant scientific publications on ultrasonographic evaluation of the optic nerve in case of brain injuries published in the last 30 years, as well as to analyze the limits of the most extensively used B-scan approach. Fifty-two papers chosen from the PubMed medical database were analyzed in this review. Our findings revealed that ocular ultrasound is an useful diagnostic tool in the management of intracranial hypertension when it exceeds a certain value or after head trauma. As a result, an ultrasound of the optic nerve can be extremely helpful in guiding diagnosis and treatment. The blooming effect is one of the most critical restrictions to consider when using B-scan ultrasonography. Since amplitude-scan ultrasound, also known as A-scan, does not have this limit, these two diagnostic techniques should always be used together for a more full, accurate, and trustworthy ultrasound examination, ensuring more data objectivity.